Festival Programming and Visitor Experience : Perceptions of four dimensions of festival programming quality by locals and tourists at the 2014 Reyjavík International Film Festival - Patricia Anna Þormar 1987- (2015)
Festival programming is an integral part of festival management and refers to the planning of scheduled activities for festival visitors. So far, however, few attempts have been made to assess the nature of festival programming and how it impacts visitor experience. Using the 2014 Reykjavík International Film Festival (RIFF) as a case study, the purpose of this dissertation is to measure the quality of the RIFF programme and explore the relationship between perceived programme quality and overall visitor experience. The study’s design is based on the six-dimensional scale developed by Yan et al. (2011) for exploring and measuring programme quality. Because festivals often contend with the conflicting interests of tourism development and community participation, the study also sought to assess any differences in locals’ and tourists’ perceptions of festival programming quality. The study’s data was collected by means of a visitor survey conducted throughout the festival, where visitors were asked to answer questions about four of six quality dimensions: diversity, incrementality, flexibility and linkage with the tourism sector, as well as rate the programme’s overall quality and their overall experience. As well as calculating the mean scores for each dimension, the study found that all dimensions have a moderate impact on programming quality, and that programming quality in turn has a considerable impact on overall visitor experience. Generally, all mean scores were relatively high, indicating a high level of satisfaction with the festival programme and festival experience. Furthermore, no meaningful difference was found between the perceptions of locals and tourists. Dagskrárgerð hátíða er mikilvægur þáttur við stjórnun hátíða, en með dagskrárgerð er átt við ferlið sem felst í því að raða niður skipulögðum dagskrárliðum hátíðarinnar svo gestir hennar fái notið þeirra. Hingað til hefur hefur lítið verið ritað um eðli dagskrárgerðar fyrir hátíðir og hvernig dagskrárgerðin hefur áhrif á upplifun hátíðargesta af ...